Cell-based analysis of CLIC5A and SLC12A2 variants associated with hearing impairment in two African families - Adadey, Samuel Mawuli; Wonkam-Tingang, Edmond; Alves de Souza Rios, Leonardo; Aboagye, Elvis Twumasi; Esoh, Kevin; Manyisa, Noluthando; De Kock, Carmen; Awandare, Gordon A.; Mowla, Shaheen; Wonkam, Ambroise (Frontiers in Genetics, 2022)
We have previously reported CLIC5A and SLC12A2 variants in two families from Cameroon and Ghana, segregating non-syndromic hearing impairment (NSHI). In this study, biological assays were performed to further functionally investigate the pathogenicity of CLIC5 [c.224T>C; p.(L75P)] and SCL12A2 [c.2935G>A: p.(E979K)] variants. Ectopic expression of the proteins in a cell model shows that compared to wild-type, both the CLIC5A and SLC12A2 variants were overexpressed. The mutant CLIC5A protein appears as aggregated perinuclear bodies while the wild-type protein was evenly distributed in the cytoplasm. Furthermore, cells transfected with the wild-type CLIC5A formed thin membrane filopodia-like protrusions which were absent in the CLIC5A mutant expressing and control cells. On the other hand, the wild-type SLC12A2 expressing cells had an axon-like morphology which was not observed in the mutant expressing and control cells. A network analysis revealed that CLIC5A can interact with at least eight proteins at the base of the stereocilia. This study has generated novel biological data associated with the pathogenicity of targeted variants in CLIC5A and SLC12A2, found in two African families, and therefore expands our understanding of their pathobiology in hearing impairment.